Joe Brainard’s I Remember, Fragmentary Life Writing and the Resistance to Narrative and Identity - Drąg, Wojciech (Text Matters: A Journal of Literature, Theory and Culture, 2019)
Paul Ricoeur declares that “being-entangled in stories” is an inherent property of the human condition. He introduces the notion of narrative identity—a form of identity constructed on the basis of a self-constructed life-narrative, which becomes a source of meaning and self-understanding. This article wishes to present chosen instances of life writing whose subjects resist yielding a life-story and reject the notions of narrative and identity. In line with Adam Phillips’s remarks regarding Roland Barthes by Roland Barthes (1975), such works—which I refer to as fragmentary life writing—emerge out of a profound scepticism about any form of “fixing” oneself and confining the variety and randomness of experience to one of the available autobiographical plots. The primary example of the genre is Joe Brainard’s I Remember (1975)—an inventory of approximately 1,500 memories conveyed in the form of radically short passages beginning with the words “I remember.” Despite the qualified degree of unity provided by the fact that all the recollections come from the consciousness of a single person, the book does not arrange its content in any discernible order—chronological or thematic; instead, the reader is confronted with a life-in-fragments. Although individual passages could be part of a coming-of-age, a coming-out or a portrait-of-the-artist-as-a-young-man narrative, Brainard is careful not to let any of them consolidate. An attempt at defining the characteristics of the proposed genre will be followed by an indication of more recent examples of fragmentary life writing and a reflection on its prospects for development